New thiazole, thiophene and 2-pyridone compounds incorporating dimethylaniline moiety: synthesis, cytotoxicity, ADME and molecular docking studies - Heba M. Metwally; Norhan M. Younis; Ehab Abdel-Latif; Ali El-Rayyes (BMC Chemistry, 2024)
Abstract Various sets of thiazole, thiophene, and 2-pyridone ring structures containing a dimethylaniline component were synthesized. Substituted thiazoles 2–3 and thiophenes 5–7 were produced by reacting thiocarbamoyl compound 4 with α-halogenated reagents in different basic conditions. Also, a series of 2-pyridone derivatives 9a–f substituted with dimethylaniline was synthesized through Michael addition of malononitrile to α,β-unsaturated nitrile derivatives 8a–f. The synthesized products were structurally proven by spectroscopic methods such as IR, 1H NMR, 13C NMR, and MS data. Furthermore, the anti-cancer efficacy of the compounds was assessed using the MTT assay on two cell lines: hepatocellular carcinoma (HepG-2) and breast cancer (MDA-MB-231). The results showed the highest growth inhibition for derivatives 2, 6, 7, and 9c, which were further examined for their IC50 values. The IC50 for compound 2 showed equipotent activity (IC50 = 1.2 µM) against the HepG-2 cell line compared to Doxorubicin (IC50 = 1.1 µM). Compounds 2, 6, 7 and 9c showed very good ADME assessments for further drug administration. Moreover, the PASS theoretical prediction for the compounds showed high antimitotic and antineoplastic activities for compounds 2, 6, 7, and 9c, as well as potent inhibition activity for the insulysin enzyme (IDE). Molecular docking stimulations were performed on CDK1/CyclinB1/CKS2 (PDB ID: 4y72) and BPTI (PDB ID: 2ra3). When docked into (PDB ID: 4y72), all of the tested compounds showed considerable inhibition, and the 2-pyridone derivative 9d had the maximum binding affinity (− 8.1223 kcal/mol). While thiophene derivative 6 offered the maximum binding affinity (− 7.5094 kcal/mol) when docked into (PDB ID: 2ra3). Graphical Abstract